Consumer behaviour towards organic products: The moderating role of environmental concern - Silvia Cachero-Martínez (Journal of Risk and Financial Management, 2020)
The pandemic caused by COVID-19 has changed the mindset of many consumers. They are increasingly aware of the risks of not caring for the planet. Before the pandemic, there was a perceived increase in collective environmental concern and sustainability, but COVID-19 has further accelerated this process and motivated more people to assume this responsibility. Thus, the health crisis could trigger the consumption of organic foods, which are foods produced through environmentally friendly agricultural methods and that have not been artificially altered. It is essential for retailers to know how these consumers of organic foods behave in order to try to modify their strategies. In this context, the objective of this research is to analyze the relationship between attitude, satisfaction, trust, purchase and word-of-mouth (WOM) intentions towards organic products. The results of a survey administered a survey to a sample of 195 consumers show that trust is influenced by satisfaction and attitude. In relation to the behavioural variables, satisfaction is the variable that has the greatest influence on purchase intentions and WOM intentions. In addition, a moderating effect of environmental concern is observed on the proposed relationships.
Keywords: 330; retail; organic products; customer satisfaction; trust; environmental concern; purchase intention